Polyfunctional group ionic polymer, preparation method and application thereof, and ion exchange membrane

A multifunctional ionic polymer with a perfluorinated main chain and phenyl end caps addresses the degradation issue in perfluorosulfonic acid resin membranes, achieving high crystallinity, low EW, and improved electrochemical performance through reduced anhydride formation and enhanced proton transport.

CN119219808APending Publication Date: 2024-12-31FOSHAN LVDONG HYDROGEN ENERGY TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411533077.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Perfluorosulfonic acid resin-based ion exchange membranes face challenges in achieving high crystallinity and low equivalent weight (EW) while maintaining thermal stability, as sulfonic acid and sulfonimide groups on side chains form anhydrides at elevated temperatures, degrading the material and reducing electrochemical performance.

Method used

A multifunctional ionic polymer with a perfluorinated main chain and phenyl group end caps is developed, incorporating sterically hindered phenyl groups to prevent anhydride formation, along with phosphonic acid groups for proton transport and improved chemical stability.

Benefits of technology

The polymer achieves high crystallinity and low EW, enhancing thermal stability, chemical stability, and electrochemical performance by reducing anhydride formation and providing proton transport channels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219808A_ABST
    Figure CN119219808A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high polymer materials, and particularly relates to a multifunctional ionic polymer, a preparation method and application thereof and an ion exchange membrane. The polyfunctional ionic polymer provided by the invention at least comprises a compound with a structural formula as shown in formula (1): # imgabs0, the main chain of the polyfunctional ionic polymer is of a perfluoro structure, the end group of the side chain is phenyl containing a substituent group, the phenyl with high steric hindrance can effectively prevent anhydride from being formed in the side chain, and anhydride formed by different side chain groups is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to a multifunctional ion polymer and a preparation method and application thereof, and an ion exchange membrane. Background Art

[0002] Perfluorosulfonic acid resin and its membrane materials have been widely used in fuel cell proton exchange membrane and membrane electrode, chlor-alkali industrial diaphragm, flow battery diaphragm, water electrolysis hydrogen production proton exchange membrane and other fields. Perfluorosulfonic acid resin is mainly obtained by copolymerization modification of tetrafluoroethylene and perfluorovinyl ether. The perfluorovinyl ether repeating unit containing sulfonic acid group gives the material ion exchange capacity; the tetrafluoroethylene repeating unit makes the material crystalline. The higher the degree of crystallinity of perfluorosulfonic acid resin, the stronger the solvent resistance and the smaller the water absorption and swelling. Conversely, perfluorosulfonic acid resin with low crystallinity or amorphous state has good solubility and processability. The perfluorosulfonic acid resin solution with low crystallinity or amorphous state is dried to form a film, and a practical ion exchange membrane can be obtained after high temperature heat treatment to promote crystallization.

[0003] The crystallization performance of ion exchange membrane materials is related to the composition of repeating units. The higher the proportion (molar amount) of tetrafluoroethylene repeating units, the higher the upper limit of the material's crystallinity. The higher the crystallinity, the better the material's barrier properties, mechanical strength, and solvent resistance, and the smaller the water absorption and swelling. The higher the proportion (molar amount) of perfluorovinyl ether repeating units containing sulfonic acid groups, the higher the content of ion exchange groups in the material, the lower the EW, the stronger the ion exchange and transmission capacity, which is beneficial to improving the electrochemical performance of the material.

[0004] Currently, more and more researchers are committed to studying and obtaining ion exchange membrane materials with high crystallinity, low EW and excellent electrochemical properties. Summary of the invention

[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems:

[0006] In order to simultaneously obtain an ion exchange resin with high crystallinity and low EW, one method is to introduce more than two ion exchange groups into the perfluorovinyl ether repeating unit. For example, two sulfonic acid groups are grafted onto the perfluorovinyl ether repeating unit in a parallel structure, or more than two sulfonimide groups are grafted through a tandem structure, or sulfonimide groups and sulfonic acid groups are grafted through a tandem structure. The side chains of the PFIA resin developed by 3M contain sulfonimide groups and sulfonic acid groups, which can achieve high crystallinity and low EW. However, the thermal stability of PFIA resin is poor. The sulfonic acid resin and sulfonimide resin on the same side chain will form anhydrides and further degrade at temperatures above 100°C, which ultimately leads to an increase in the EW of the material and a sharp attenuation of the electrochemical performance. The degradation process of the PFIA resin side chain is shown in the following formula:

[0007]

[0008] Regardless of whether melt molding or solution processing is used, PFIA resin needs to be treated at a temperature above 140°C for a period of time, which greatly limits the application of PFIA resin in the field of ion exchange membranes.

[0009] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, an embodiment of the present invention provides a multifunctional ionic polymer, the main chain of which is a perfluorinated structure, the end group of the side chain is a phenyl group containing a substituent, and the highly sterically hindered phenyl group can effectively avoid the formation of anhydride inside the side chain and greatly reduce the formation of anhydride by different side chain acidic groups.

[0010] The multifunctional ionic polymer of the embodiment of the present invention comprises at least one compound having a structural formula as shown in formula (1):

[0011]

[0012] Wherein, x is 3 to 14, y is 1 to 10000; z×100%≥1%; a=a positive integer of 0 to 6, b=a positive integer of 2 to 5;

[0013] R 0 Selected from OM, F, Cl, Br, I or NH 2 Any one of R 1 is an alkylene group, a fluoroalkylene group or a direct bond; R 2 Selected from C 1 ~C 6 Alkyl, C 1 ~C 6 Fluorinated alkyl, M or PO(OM) 2 Any one of R 5 and R 6 Each independently selected from H, F, Cl, Br, C 1 ~C 6 Alkyl or C 1 ~C 6 any one of the fluoroalkyl groups; wherein M is selected from any one of hydrogen, lithium, sodium, potassium, rubidium, cesium, ammonium ion or tertiary ammonium cation.

[0014] The advantages and technical effects brought by the multifunctional ionic polymer of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, the main chain of the multifunctional ionic polymer is a perfluorinated structure, and the end group of the side chain is a phenyl group containing a substituent. The highly sterically hindered phenyl group can effectively avoid the formation of anhydride inside the side chain and greatly reduce the formation of anhydride by different side chain acidic groups; 2. In the embodiment of the present invention, the alkoxy group on the benzene ring can be converted into a hydroxyl group under acidic conditions, the methoxy group has strong reactivity, and the phenolic hydroxyl group connected to the benzene ring has an excellent free radical quenching effect, which can improve the chemical stability of the multifunctional ionic polymer; 3. In the embodiment of the present invention, the phosphonic acid group has proton transport ability and proton compensation ability, has good water retention ability at high temperature, is suitable for high temperature working conditions of ion exchange membranes, and the multi-ion transport channel formed with the sulfonimide group and / or sulfonic acid group in the multifunctional ionic polymer can reduce the proton transport energy barrier and improve the electrochemical properties of the material.

[0015] In some embodiments, the EW of the multifunctional ionic polymer is 400-2000 g / mol.

[0016] In some embodiments, the multifunctional ionic polymer includes a first polymer and a second polymer;

[0017] The structural formula of the first polymer is shown in formula (2):

[0018]

[0019] Among them a, b, x, y, z, M, R 1 , R 5 , R 6 Same as in formula (1), R 4 Selected from M, C 1 ~C 6 Alkyl, C 1 ~C 6 Any one of the fluoroalkyl groups;

[0020] The structural formula of the second polymer is shown in formula (3):

[0021]

[0022] Among them a, b, x, y, z, M, R 1 , R 5 , R 6 Same as in formula (1), R 7 Selected from PO(OH) 2 .

[0023] The present invention also provides a method for preparing a multifunctional ionic polymer, comprising the following steps:

[0024] (1) dispersing a resin raw material and a functionalizing agent in a first organic medium, and then adding an organic base to carry out a nucleophilic substitution reaction to obtain a crude product dispersion;

[0025] (2) pouring the crude product dispersion obtained in step (1) into a poor solvent for separation to obtain a crude polymer product, and drying the crude polymer product to obtain an intermediate product;

[0026] (3) The intermediate obtained in step (2) is transformed by an alkaline solution and / or an acid solution, washed with water and / or a poor solvent, and then dried to obtain a first polymer.

[0027] In some embodiments, in step (1), the resin raw material is a sulfonyl halide resin, and the functionalizing agent is a sulfonamide compound; or, the resin raw material is a sulfonamide resin, and the functionalizing agent is a sulfonyl halide compound;

[0028] And / or, in the step (1), the first organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetramethyl sulfoxide, hexamethylphosphoric triamide, N-methylpyrrolidone or tetrahydrofuran;

[0029] And / or, in the step (1), the organic base comprises at least one of an organic amine or a nitrogen heterocyclic compound that does not contain a nitrogen heterocyclic ring, and the organic amine that does not contain a nitrogen heterocyclic ring comprises C 1 ~C 20 Alkyl and / or C 6 ~C 20 At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group, wherein the nitrogen heterocyclic compound comprises C 1 ~C 20 Alkyl and / or C 6 ~C 20 At least one of pyridine, imidazole, pyrrole, piperidine or piperazine substituted with an aromatic group;

[0030] And / or, in the step (1), the mass ratio of the resin raw material, the functionalizing agent and the organic base is 100:1-400:1-800;

[0031] And / or, in the step (1), the temperature of the nucleophilic substitution reaction is 50 to 180° C., the reaction pressure is 0.1 to 10 MPa, and the reaction time is 1 h to 120 h;

[0032] and / or, in step (2) and / or step (3), the poor solvent comprises at least one of lipids, aromatic hydrocarbons, alkanes, ketones or halogenated hydrocarbons;

[0033] And / or, in step (3), the alkaline solution includes at least one of lithium hydroxide solution, rubidium hydroxide solution, cesium hydroxide solution, ammonia solution, NaOH solution, and KOH solution, and the acid solution includes at least one of sulfuric acid solution, nitric acid solution, phosphoric acid solution, or hydrochloric acid solution;

[0034] And / or, in the step (3), the temperature of the transformation treatment is 20 to 100° C., and the time of the transformation treatment is 1 to 48 hours.

[0035] In some embodiments, the step (1) comprises: dispersing the resin raw material in a first organic medium to obtain a resin raw material dispersion, dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution, mixing the resin raw material dispersion and the functionalizing agent solution, and then adding an organic base to perform a nucleophilic substitution reaction to obtain a crude product dispersion;

[0036] Preferably, the second organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethyl sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone or tetrahydrofuran.

[0037] In some embodiments, the method further comprises step (4): adding the first polymer and the phosphonation agent into a third medium for a phosphonation reaction to obtain a second polymer;

[0038] Preferably, the third medium comprises at least one of water, polyols, fatty alcohols, DMF, DMAc, DMSO or tetrahydrofuran;

[0039] And / or, the phosphonating agent includes at least one of orthophosphoric acid, oligophosphoric acid, alkali metal salt or ammonium salt of oligophosphoric acid, sodium hexametaphosphate, phosphorus trichloride, phosphorus pentachloride, phosphorus oxychloride, and triester phosphite compound;

[0040] And / or, the phosphonation reaction is carried out under the action of a catalyst, the catalyst comprises at least one of urea, urea derivatives, guanidine, guanidine derivatives, trimethylamine or triethylamine, and the mass ratio of the first polymer, the phosphonation agent and the catalyst is 1:0.2-10:0-15;

[0041] And / or, the temperature of the phosphonation reaction is 20 to 180° C., and the time of the phosphonation reaction is 1 min to 24 h.

[0042] In some embodiments, in step (2), the structure of the intermediate is as shown in formula (1), wherein a, b, x, y, z, M, R 1 , R 5 , R 6 Same as in formula (1), R 0 Selected from F, Cl, Br, I or NH 2 , R 2 Selected from M, C~C 6 Alkyl, C~C 6 Any one of the fluoroalkyl groups.

[0043] In some embodiments, the intermediate and the phosphonating agent are added to a third medium for a phosphonating reaction to obtain a third polymer, the structural formula of the third polymer is shown in formula (4):

[0044]

[0045] Among them, a, b, x, y, z, M, R 0 , R 1 , R 5 , R 6 Same as in the intermediate, R 8 PO(OM) 2 , the intermediate product R 2 For H.

[0046] The embodiments of the present invention further provide the use of the above multifunctional ionic polymer or the multifunctional ionic polymer prepared by the above preparation method in an ion exchange membrane.

[0047] The embodiment of the present invention further provides an ion exchange membrane, comprising the above-mentioned multifunctional ion polymer or the multifunctional ion polymer prepared by the above-mentioned preparation method.

[0048] The present invention also provides a method for preparing an ion exchange membrane, comprising the following steps:

[0049] (a) dispersing the multifunctional ionic polymer as claimed in claim 1 or the multifunctional ionic polymer prepared by the preparation method as claimed in claim 1 in a solvent to obtain a resin slurry;

[0050] (b) forming and drying the resin slurry obtained in step (a) to obtain an ion exchange membrane.

[0051] The embodiments of the present invention also provide the use of the above-mentioned ion exchange membrane or the ion exchange membrane prepared by the above-mentioned preparation method in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 is the infrared spectrum of PFMA-20;

[0053] Figure 2 are cross-sectional SEM images of PEM-20 and D-PEM-20;

[0054] Figure 3 It is the polarization curve diagram of PEM-20H and D-PEM-20H. DETAILED DESCRIPTION

[0055] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0056] The multifunctional ionic polymer of the embodiment of the present invention comprises at least one compound having a structural formula as shown in formula (1):

[0057]

[0058] Wherein, x is 3 to 14, y is 1 to 10000; z×100%≥1%; a=a positive integer of 0 to 6, b=a positive integer of 2 to 5;

[0059] R 0 Selected from OM, F, Cl, Br, I or NH 2 Any one of R 1 is an alkylene group, a fluoroalkylene group or a direct bond; R 2 Selected from C 1 ~C 6 Alkyl, C 1 ~C 6 Fluorinated alkyl, M or PO(OM) 2 Any one of R 5 and R 6 Each independently selected from H, F, Cl, Br, C 1 ~C 6 Alkyl or C 1 ~C 6 any one of the fluoroalkyl groups; wherein M is selected from any one of hydrogen, lithium, sodium, potassium, rubidium, cesium, ammonium ion or tertiary ammonium cation.

[0060] The multifunctional ionic polymer of the embodiment of the present invention has a main chain of a perfluorinated structure, and the end group of the side chain is a phenyl group containing a substituent. The highly sterically hindered phenyl group can effectively avoid the formation of anhydride inside the side chain and greatly reduce the formation of anhydride by different side chain acidic groups; the alkoxy group on the benzene ring can be converted into a hydroxyl group under acidic conditions, the methoxy group has strong reactivity, and the phenolic hydroxyl group connected to the benzene ring has an excellent free radical quenching effect, which can improve the chemical stability of the multifunctional ionic polymer; the phosphonic acid group has proton transport ability and proton compensation ability, has good water retention ability at high temperature, is suitable for high temperature working conditions of ion exchange membranes, and the multi-ion transport channel formed with the sulfonimide group and / or sulfonic acid group in the multifunctional ionic polymer can reduce the proton transport energy barrier and improve the electrochemical properties of the material.

[0061] In some embodiments, preferably, z×100% is the grafting rate of the multifunctional side chains, preferably, the grafting rate is ≥1%, more preferably ≥10%, and further preferably ≥50%. The higher the grafting rate, the higher the proportion of the multifunctional side chains.

[0062] In some embodiments, preferably, the R 1 Selected from methylene, ethylene, propylene, butylene, perfluoromethylene, perfluoroethylene, CH(CH 3 ) or direct bonding. More preferably, the R 1 Select as direct bonding.

[0063] In some embodiments, preferably, the R 2 Selected from trifluoromethyl, methyl, ethyl, isopropyl, n-butyl, 3-methylbutyl, M or PO(OM) 2 More preferably, the R 2 Selected from H or PO(OH) 2 .

[0064] In some embodiments, preferably, the R 5 and R 6 Each independently selected from any one of H, F, methyl, ethyl, n-propyl, isopropyl, tert-butyl, n-butyl, and trifluoromethyl. More preferably, the R 5 and R 6 Each independent H.

[0065] In some embodiments, preferably, the EW of the multifunctional ionic polymer is 400 to 2000 g / mol. Further preferably, the EW of the multifunctional ionic polymer is 500 to 1500 g / mol. More preferably, the EW of the multifunctional ionic polymer is 600 to 1200 g / mol.

[0066] In the embodiment of the present invention, the EW value of the ionic polymer is preferably selected so that the polymer has a higher ion exchange capacity, lower water swelling, and better dimensional stability and mechanical properties; if the EW value is too high, the ion exchange capacity (IEC) of the polymer material is low, the ion exchange capacity and ion transport capacity are poor, and when applied to a proton exchange membrane or a membrane electrode, the electrochemical performance of the proton exchange membrane or the membrane electrode will be poor; if the EW value is too low, the water swelling of the polymer material is difficult to control, and excessive water swelling will sharply reduce the dimensional stability and mechanical properties of the material.

[0067] In some embodiments, preferably, the multifunctional ionic polymer includes a first polymer and a second polymer.

[0068] The structural formula of the first polymer is shown in formula (2):

[0069]

[0070] Among them a, b, x, y, z, M, R 1 , R 5 , R 6 Same as in formula (1), R 4 Selected from M, C 1 ~C 6 Alkyl, C 1 ~C 6 Any one of the fluoroalkyl groups; preferably, the R 4 is selected from any one of H, methyl, ethyl, n-propyl, isopropyl, n-butyl, 3-methylbutyl, tert-butyl or trifluoromethyl; further preferably, the R 4 is selected from any one of H or methyl; more preferably, the R 4 Selected from H.

[0071] The structural formula of the second polymer is shown in formula (3):

[0072]

[0073] Among them a, b, x, y, z, M, R 1 , R 5 , R 6 Same as in formula (1), R 7 Selected from PO(OH) 2 .

[0074] The present invention also provides a method for preparing a multifunctional ionic polymer, comprising the following steps:

[0075] (1) dispersing a resin raw material and a functionalizing agent in a first organic medium, and then adding an organic base to carry out a nucleophilic substitution reaction to obtain a crude product dispersion;

[0076] (2) pouring the crude product dispersion obtained in step (1) into a poor solvent for separation to obtain a crude polymer product, and drying the crude polymer product to obtain an intermediate product;

[0077] (3) The intermediate obtained in step (2) is transformed by an alkaline solution and / or an acid solution, washed with water and / or a poor solvent, and then dried to obtain a first polymer.

[0078] In some embodiments, in step (1), the resin raw material is a sulfonyl halide resin, and the functionalizing agent is a sulfonamide compound; or, the resin raw material is a sulfonamide resin, and the functionalizing agent is a sulfonyl halide compound.

[0079] When the resin raw material is a sulfonyl halide resin and the functionalizing agent is a sulfonamide compound, the synthesis route is as shown in formula (5):

[0080]

[0081] When the resin raw material is a sulfonamide resin and the functionalizing agent is a sulfonyl halide compound, the synthesis route is as shown in formula (6):

[0082]

[0083] In formula (5) and formula (6), a, b, x, y, R 1 , R 5 , R 6 Same as the above formula (2); X is F, Cl, Br or I, preferably F or Cl, and the reactivity of sulfonyl chloride group and sulfonyl fluoride group is relatively high; R 3 Any one selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl or trifluoromethyl, preferably any one selected from H, methyl, ethyl, isopropyl or n-butyl, more preferably selected from methyl, the methoxy group has good chemical stability during the reaction and is easily acidified to a hydroxyl group.

[0084] In some embodiments, preferably, the ratio of x to (z+1) in the sulfonyl halide resin and / or the sulfonamide resin is 1 to 10, preferably 2 to 8, more preferably 3 to 6. Preferably, the sulfonamide resin is obtained by reacting a sulfonyl halide resin with ammonia.

[0085] In some embodiments, preferably, in the step (1), the first organic medium includes at least one of acetonitrile, toluene, xylene, carbitol, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetramethyl sulfoxide, hexamethylphosphoric acid triamide, N-methylpyrrolidone (NMP) or tetrahydrofuran. Further preferably, the first organic medium includes at least one of acetonitrile, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, DMSO, DMF, DMAc or NMP. More preferably, the first organic medium includes at least one of acetonitrile, dioxane, DMSO, DMF, DMAc or hexafluorobenzene.

[0086] In the embodiment of the present invention, the type of the first organic medium is preferably selected. The solubility of sulfonamide resin is better than that of sulfonyl fluoride resin, and it can be dissolved in fluorocarbon solvents and non-fluorine solvents. Sulfonyl fluoride resin can only swell in fluorocarbon solvents, acetonitrile, dioxane and other solvents. During the reaction, the sulfonyl fluoride resin remains in a swollen state for grafting reaction.

[0087] In some embodiments, preferably, the functionalizing agent is a sulfonamide compound, and the sulfonamide compound includes 2-methoxybenzenesulfonamide, 3-methoxybenzenesulfonamide, 4-methoxybenzenesulfonamide, 2-fluoro-4-methoxybenzenesulfonamide, 2-fluoro-5-methoxybenzenesulfonamide, 2-chloro-5-methoxybenzenesulfonamide, 3-fluoro-4-methoxybenzenesulfonamide, 3-chloro-4-methoxybenzenesulfonamide, 3-bromo-4-methoxybenzenesulfonamide, 4-trifluoromethoxybenzenesulfonamide, 2-trifluoromethoxybenzenesulfonamide, 3-trifluoromethoxybenzenesulfonamide, 5-fluoro-2-methoxybenzenesulfonamide, 5-bromo-2-methoxybenzenesulfonamide, 2,4-difluoro-6-methoxybenzenesulfonamide, 2,6-dimethyl-4-methoxybenzenesulfonamide. amide, 2-difluoromethoxybenzenesulfonamide, 3-difluoromethoxybenzenesulfonamide, 4-(difluoromethoxy)benzenesulfonamide, 5-ethyl-2-methoxy-benzenesulfonamide, 5-isopropyl-2-methoxy-benzenesulfonamide, 5-tert-butyl-2-methoxybenzenesulfonamide, 4-methoxy-3-methyl-benzenesulfonamide, 4-ethoxybenzenesulfonamide, 3-ethoxybenzenesulfonamide, 2-ethoxybenzenesulfonamide, 5-bromo-2-ethoxy-benzenesulfonyl, 4-isopropoxybenzenesulfonamide, 5-tert-butyl-2-propoxybenzenesulfonamide, 4-isopropoxy-3-methylbenzenesulfonyl, 4-butoxybenzenesulfonamide, 4-(3-methylbutoxy)benzenesulfonamide, 4-hydroxybenzenesulfonamide, and (3-methoxyphenyl)methanesulfonamide. Further preferably, the sulfonamide compound includes at least one of 4-methoxybenzenesulfonamide, 2-fluoro-4-methoxybenzenesulfonamide, 3-fluoro-4-methoxybenzenesulfonamide, 2-fluoro-5-methoxybenzenesulfonamide, 2,6-dimethyl-4-methoxybenzenesulfonamide, 4-methoxy-3-methyl-benzenesulfonamide, 4-ethoxybenzenesulfonamide, 3-ethoxybenzenesulfonamide, 4-isopropoxybenzenesulfonamide, 4-isopropoxy-3-methylbenzenesulfonyl, 4-butoxybenzenesulfonamide, 4-(3-methylbutoxy)benzenesulfonamide, and 4-hydroxybenzenesulfonamide. More preferably, the sulfonamide compound includes at least one of 4-methoxybenzenesulfonamide or 3-methoxybenzenesulfonamide.

[0088] In some embodiments, preferably, the functionalizing agent is a sulfonyl halide compound, and the sulfonyl halide compound includes at least one of a sulfonyl chloride compound or a sulfonyl fluoride compound. Further preferably, the sulfonyl fluoride compound includes at least one of 4-methoxybenzenesulfonyl fluoride or 3-methoxybenzenesulfonyl fluoride, and the sulfonyl fluoride compound includes at least one of 4-methoxybenzenesulfonyl chloride or 3-methoxybenzenesulfonyl chloride.

[0089] In some embodiments, preferably, in step (1), the organic base comprises at least one of an organic amine or a nitrogen heterocyclic compound that does not contain a nitrogen heterocyclic ring, and the organic amine that does not contain a nitrogen heterocyclic ring comprises C 1 ~C20 Alkyl and / or C 6 ~C 20 At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group, wherein the nitrogen heterocyclic compound comprises C 1 ~C 20 Alkyl and / or C 6 ~C 20 At least one of aryl-substituted pyridine, imidazole, pyrrole, piperidine or piperazine. Further preferably, the organic base includes triethylamine, tripropylamine, triisopropylamine, tributylamine, tripentylamine, trihexylamine, triphenylamine, dodeca-tertiary amine, octadecyl tertiary amine, N,N-dimethylcyclohexylamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dibutylethylenediamine, N,N-dimethylhexylamine, triethylethylenediamine, tetramethylethylenediamine, tetramethyl-1,3-propylenediamine, tetramethyl-1,6-hexanediamine, 2,5-dimethyl-p-phenylenediamine, N,N'-dibutylphenylenediamine, N,N-dimethyldipropylenetriamine. More preferably, the organic base includes at least one of triethylamine, tripropylamine, triisopropylamine, tributylamine or trihexylamine.

[0090] In some embodiments, preferably, in the step (1), the mass ratio of the resin raw material, the functionalizing agent and the organic base is 100:1-400:1-800. Further preferably, the mass ratio of the resin raw material, the functionalizing agent and the organic base is 100:10-200:10-600. More preferably, the mass ratio of the resin raw material, the functionalizing agent and the organic base is 100:30-150:100-400.

[0091] In some implementations, preferably, in the step (1), the temperature of the nucleophilic substitution reaction is 50 to 180°C, more preferably 60 to 180°C, and even more preferably 80 to 180°C.

[0092] In the embodiments of the present invention, the reaction temperature is preferably selected, and the reaction temperature is not higher than the boiling point of each component. The reaction system can be reacted at a higher temperature by condensation reflux. A higher reaction temperature is beneficial to accelerating the reaction rate and reducing the reaction time.

[0093] In some implementations, preferably, in step (1), the pressure of the nucleophilic substitution reaction is 0.1-10 MPa, such as 0.1 MPa, 1 MPa, 5 MPa, 10 MPa, etc. When reacting in a pressure vessel, the reaction temperature can be increased by increasing the pressure in the vessel to further increase the reaction rate.

[0094] In some implementations, preferably, in the step (1), the time of the nucleophilic substitution reaction is 1 h to 120 h, more preferably 12 h to 96 h, and more preferably 18 h to 72 h.

[0095] In the embodiments of the present invention, the reaction rates of the resin raw material and the functionalizing agent at different temperatures are different, and sufficient reaction time can improve the degree of reaction. If the reaction time is too short, the degree of reaction is low and the grafting rate of the product is low; if the reaction time is too long, the degree of reaction is basically unchanged and the grafting rate will not be further improved.

[0096] In some implementations, preferably, in step (2) and / or in step (3), the poor solvent includes at least one of lipids, aromatic hydrocarbons, alkanes, ketones or halogenated hydrocarbons. Further preferably, the poor solvent includes at least one of ethyl acetate, toluene, n-hexane, n-pentane, cyclohexane, acetone, butanone, and dichloromethane. More preferably, the poor solvent includes at least one of n-hexane, cyclohexane, acetone or butanone. Lipid solvents are easily hydrolyzed into fatty acids and fatty alcohols by the acidic action of fluoropolymers; acetone and butanone have good miscibility with water and are preferred poor reagents; n-hexane and cyclohexane have poor miscibility with water and high-polarity organic solvents, but they have a great difference in polarity with polymers and have a good precipitation effect. To address the problem of poor miscibility, ketones, halogenated hydrocarbons, aromatic hydrocarbons and alkanes can be mixed as poor reagents.

[0097] In some embodiments, preferably, the alkaline solution includes at least one of lithium hydroxide solution, rubidium hydroxide solution, cesium hydroxide solution, ammonia solution, NaOH solution, and KOH solution, and the acid solution includes at least one of sulfuric acid solution, nitric acid solution, phosphoric acid solution, or hydrochloric acid solution. Further preferably, the concentration of the alkaline solution is 0.1 to 8 mol / L, the concentration of the acid solution is 1 mol / L, and the concentration of the acid solution is preferably 2 to 24 mol / L, more preferably 4 to 12 mol / L, such as the concentration of the acid solution is 4 mol / L, 6 mol / L, or 12 mol / L. The main function of the alkaline solution is to convert the unreacted -SO 2 X and -SO 2 NH 2 Transformation to -SO 3 Na, -SO 3 Li, -SO 3 Rb, -SO 3 NH 4 、-SO 3 Cs, or -SO 3 K; The alkoxy group on the side chain phenyl group can be completely acidified to hydroxyl group in high concentration (≥4mol / L) hydrochloric acid solution. When the acid concentration is lower than 2mol / L, the alkoxy group basically does not react and can only replace the cations bound to the sulfonic acid group and sulfonimide group with hydrogen ions, or replace the unreacted -SO 2 NH 2 Transformation to -SO 3 H.

[0098] In some embodiments, preferably, the step (1) comprises: dispersing the resin raw material in a first organic medium to obtain a resin raw material dispersion, dispersing the functionalizing agent in a second organic medium to obtain a functionalizing agent solution, mixing the resin raw material dispersion and the functionalizing agent solution, and then adding an organic base to perform a nucleophilic substitution reaction to obtain a crude product dispersion.

[0099] In some embodiments, preferably, the resin raw material dispersion is a resin raw material swollen in a first organic medium, or an emulsion consisting of the resin raw material and the first organic medium, or a solution consisting of the resin raw material and the first organic medium.

[0100] In some embodiments, preferably, the mass content of the resin raw material in the resin raw material dispersion is 0.1 to 30%, more preferably 0.5 to 20%, and even more preferably 1 to 10%.

[0101] In the embodiment of the present invention, the mass content of the resin raw material in the resin raw material dispersion is preferably selected. If the mass content is low, too much solvent is consumed during the preparation process. If the mass content is high, the resin raw material is difficult to disperse, which is not conducive to the preparation of the polymer.

[0102] In some embodiments, preferably, the second organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethyl sulfoxide, hexamethylphosphoric acid triamide, N-methylpyrrolidone or tetrahydrofuran. Further preferably, the second organic medium comprises at least one of DMSO, DMF, DMAc or NMP.

[0103] In some embodiments, preferably, the mass content of the functionalizing agent in the functionalizing agent solution is 1 to 80%, more preferably 10 to 60%, and even more preferably 10 to 40%.

[0104] The first organic medium, the second organic medium and the organic base all have a dispersing effect on the resin raw material and the functionalizing agent, and the total mass of the first organic medium, the second organic medium and the organic base is m 1 , the total mass of the resin raw material and the functionalization reagent is m 2 . m 1 :m 2 =100:1-60, preferably 100:3-40, more preferably 100:5-30.

[0105] In some embodiments, preferably, the first organic medium, the second organic medium and the organic base are preferably selected from anhydrous grade reagents (the water content of the reagents is ≤50 ppm).

[0106] In some embodiments, preferably, in step (3), the temperature of the transformation treatment is 20-100°C, such as 20°C, 25°C, 30°C, 50°C, 100°C, etc., and the time of the transformation treatment is 1-48h.

[0107] In some embodiments, preferably, in step (2) and / or step (3), the drying method can be freeze drying, forced air drying or vacuum drying.

[0108] In some embodiments, the method further includes step (4): adding the first polymer and the phosphonating agent into a third medium to carry out a phosphonating reaction to obtain a second polymer.

[0109] In some embodiments, preferably, the molar ratio of hydroxyl groups to phosphonic acid groups in the second polymer is 0 to 10000:100, preferably 0 to 1000:100, and more preferably 0 to 100:100.

[0110] In some embodiments, preferably, the third medium comprises at least one of water, polyols, fatty alcohols, DMF, DMAc, DMSO or tetrahydrofuran. Further preferably, the third medium comprises at least one of ethanol, isopropanol, n-propanol, n-hexanol, tetramethyl sulfoxide, hexamethylphosphoric acid triamide, NMP, DMF, DMAc or DMSO. More preferably, the third medium comprises at least one of DMF, DMAc or DMSO.

[0111] In some embodiments, preferably, the phosphonating agent includes at least one of orthophosphoric acid, oligophosphoric acid, alkali metal salt or ammonium salt of oligophosphoric acid, sodium hexametaphosphate, phosphorus trichloride, phosphorus pentachloride, phosphorus oxychloride, and triester phosphite. Further preferably, the phosphonating agent includes at least one of orthophosphoric acid, trimethyl phosphite, and triethyl phosphite. More preferably, the phosphonating agent includes orthophosphoric acid.

[0112] In some embodiments, preferably, the phosphonation reaction is carried out under the action of a catalyst, and the catalyst includes at least one of urea, urea derivatives, guanidine, guanidine derivatives, trimethylamine or triethylamine. Further preferably, the catalyst includes urea and dicyandiamide.

[0113] The embodiment of the present invention preferably selects the phosphonating agent and catalyst. Orthophosphoric acid has the advantages of low viscosity (relative to polyphosphoric acid), low cost, wide source and stable chemical properties, and the reaction system has no requirements on water content and gas atmosphere, and the reaction conditions are mild; polyphosphoric acid has high viscosity; chlorine-containing phosphide has poor stability and harsh reaction conditions; the intermediate polymer obtained by the reaction of triester phosphite is grafted with alkaline phosphonate functional groups, which needs to be further acidified to obtain phosphonic acid groups, which increases the complexity of the reaction. Urea and dicyandiamide have wide sources, low costs and high catalytic efficiency. The reaction system composed of orthophosphoric acid, urea and dicyandiamide has the advantages of safety, high efficiency and low cost, and is the most preferred reaction system.

[0114] In some embodiments, preferably, the mass ratio of the first polymer, the phosphonating agent and the catalyst is 1: 0.2-10: 0-15, more preferably 1: 0.3-5: 0.2-5: 0.2-5, and more preferably 1: 0.5-3: 0.5-3: 0.5-3.

[0115] If the orthophosphoric acid content is too low, the number of cut-off phosphonic acid groups in the product will be limited. If the orthophosphoric acid content is too high, it will cause unnecessary waste and make dispersion difficult. No catalyst or low catalyst content will lead to low reaction rate and low reaction degree. Too much catalyst will cause unnecessary waste and produce nitrogen-containing by-products.

[0116] In some embodiments, preferably, the temperature of the phosphonation reaction is 20-180°C, such as 40°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, etc.; the time of the phosphonation reaction is 1 min to 24 h, such as 1 min, 3 min, 7 min, 21 min, 0.5 h, 10 h, 20 h, 24 h, etc. Further preferably, the temperature of the phosphonation reaction is 80-160°C, and the time of the phosphonation reaction is 3 min to 8 h.

[0117] In some embodiments, preferably, the first polymer, the phosphonating agent and the catalyst account for 0.1 to 40% of the mass of the third medium, more preferably 0.5 to 30%, and even more preferably 1 to 20%.

[0118] In some embodiments, preferably, the first polymer is first dispersed in a third medium to obtain a first solution, and then a catalyst and a phosphonating agent are added to react. The concentration of the first solution is 1 mg / mL to 300 mg / mL, preferably 5 mg / mL to 250 mg / mL, and more preferably 5 mg / mL to 200 mg / mL.

[0119] In some embodiments, preferably, after the phosphonation reaction is completed, the mixture is cooled to room temperature, then added to a poor solvent for precipitation and washing, and dried to obtain a second polymer; the poor solvent includes at least one of water, acetone, butanone, tetrahydrofuran, and esters.

[0120] In some embodiments, in step (2), the structure of the intermediate is as shown in formula (1), wherein a, b, x, y, z, M, R 1 , R 5 , R 6 Same as in formula (1), R 0 Selected from F, Cl, Br, I or NH 2 , R 2 Selected from M, C~C 6 Alkyl, C~C 6 Any one of the fluoroalkyl groups.

[0121] In some embodiments, preferably, the intermediate and the phosphonating agent are added to a third medium for a phosphonating reaction to obtain a third polymer, wherein the third polymer has a structural formula as shown in formula (4):

[0122]

[0123] Among them, a, b, x, y, z, M, R 0 , R 1 , R 5 , R 6 Same as the intermediate product, R 8 PO(OM) 2 , the intermediate product R 2 For H.

[0124] The phosphonation reaction conditions of the third polymer are the same as those of the second polymer, and are not described in detail herein.

[0125] The embodiments of the present invention further provide the use of the above multifunctional ionic polymer or the multifunctional ionic polymer prepared by the above preparation method in an ion exchange membrane.

[0126] The embodiment of the present invention further provides an ion exchange membrane, comprising the above-mentioned multifunctional ion polymer or the multifunctional ion polymer prepared by the above-mentioned preparation method.

[0127] An embodiment of the present invention provides an ion exchange membrane, which includes a multifunctional ion polymer of an embodiment of the present invention. In the embodiment of the present invention, the sulfonimide functional group of the ion exchange membrane has the strongest gas phase acidity, improves the ion transmission capacity of the material at high temperature, can improve the proton conductivity of the ion exchange membrane, and is suitable for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis, and flow battery diaphragms. The phenolic hydroxyl group on the side chain can act as a free radical quencher to improve the chemical stability of the material, and the phosphonic acid group on the side chain can synergize with other acidic ion groups to improve the ion transmission capacity.

[0128] In some embodiments, preferably, the membrane thickness of the ion exchange membrane is 5 to 450 μm; preferably 6 to 300 μm, and more preferably 7 to 200 μm.

[0129] In some embodiments, preferably, the ion exchange capacity of the ion exchange membrane is 0.1 to 4 mmol / g, preferably 0.15 to 2.5 mmol / g, and more preferably 0.2 to 2.0 mmol / g.

[0130] In some embodiments, preferably, the ion exchange membrane further comprises a reinforcement membrane, and the reinforcement membrane is a porous membrane, and the material of the porous membrane comprises at least one of non-fluorinated polyolefins, fluorinated polymer materials and aromatic polymers. Further preferably, the non-fluorinated polyolefin comprises at least one of polyethylene, polypropylene or ethylene-propylene copolymer; the fluorinated polymer material comprises at least one of polytetrafluoroethylene, tetrafluoroethylene hexafluoropropylene copolymer, tetrafluoroethylene propylene copolymer, ethylene tetrafluoroethylene copolymer, tetrafluoroethylene hexafluoropropylene ethylene copolymer, polyvinylidene fluoride, vinylidene fluoride hexafluoropropylene copolymer, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer, vinylidene fluoride tetrafluoroethylene hexafluoropropylene copolymer, polyvinyl fluoride, polychlorotrifluoroethylene, ethylene chlorotrifluoroethylene copolymer; the aromatic polymer membrane comprises at least one of polyaryletherketone, polysulfone, polyethersulfone, polyethersulfoneketone, polybenzimidazole, polyaromatic amide, polyimide or polyetheretherketone.

[0131] The present invention also provides a method for preparing an ion exchange membrane, comprising the following steps:

[0132] (a) dispersing the multifunctional ionic polymer as claimed in claim 1 or the multifunctional ionic polymer prepared by the preparation method as claimed in claim 1 in a solvent to obtain a resin slurry;

[0133] (b) forming and drying the resin slurry obtained in step (a) to obtain an ion exchange membrane.

[0134] In the embodiment of the present invention, an ion exchange membrane is obtained by solution molding and drying. The obtained ion exchange membrane has good flatness, uniform thickness distribution, and better performance; the process is simple, easy to operate, and has high production efficiency, which is convenient for wide application in industrial production. The dispersion in the preparation process can also be used to prepare coatings, hydrogels and adhesives for porous membranes such as desalination membranes and ultra / microfiltration membranes, as well as various fabrics and protective equipment such as surgical gloves, protective clothing, and sterile sheets, and has a wide range of applications.

[0135] In some embodiments, preferably, in the step (a), the dispersion temperature is 10 to 240°C; and / or the dispersion time is 0.1 to 24 hours; and / or the dispersion pressure is 0.1 to 20 MPa; and / or the dispersion is carried out by stirring, shaking or ultrasound.

[0136] In some embodiments, preferably, in step (a), the solvent includes at least one of water, a high boiling point organic solvent, tetrahydrofuran, and a lower aliphatic alcohol. Further preferably, the high boiling point organic solvent includes at least one of ethylene glycol, propylene glycol, glycerol, DMF, DMAC, DMSO, hexamethylphosphoric acid triamide, and NMP; and the lower aliphatic alcohol includes at least one of methanol, ethanol, isopropanol, n-propanol, and n-butanol.

[0137] In some embodiments, preferably, in the step (b), the forming comprises at least one of casting, pouring or coating; and / or the temperature of the drying treatment is 20 to 180°C.

[0138] In some embodiments, preferably, the step (b) further comprises coating the resin slurry on one side or both sides of the reinforcement layer, and obtaining the ion exchange membrane after drying; preferably, the coating comprises at least one of dipping, blade coating, and slit coating.

[0139] The embodiments of the present invention also provide the use of the above-mentioned ion exchange membrane or the ion exchange membrane prepared by the above-mentioned preparation method in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.

[0140] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0141] Example 1

[0142] (1) Weighing 1 g of sulfonyl fluoride resin 1 and swelling it in a first organic medium;

[0143] (2) dispersing a certain amount of 4-methoxybenzenesulfonamide in a certain amount of a second organic medium to obtain a functionalizing agent solution;

[0144] (3) The swollen sulfonyl fluoride resin and the functionalizing agent solution were mixed in a flask, and then 4 g of triethylamine was added dropwise at 20°C. The reaction system was then heated to 80°C and stirred for 48 hours. After the reaction was completed, the reaction system was poured into acetone to separate the polymer solid, which was washed alternately with acetone and cyclohexane, and then placed in a 4 mol / L sodium hydroxide solution for sodiumization at 90°C for 24 hours. The sodiumized polymer solid was placed in 12 mol / L concentrated hydrochloric acid for acidification at a temperature of 40°C for 24 hours. The acidified solid product was washed with acetone until the pH value of the washing solution reached 6.5 to 7.5. The multifunctional ionic polymer solid was obtained by vacuum drying at 45°C for 48 hours.

[0145] Wherein, the structural formula of sulfonyl fluoride resin 1 is:

[0146]

[0147] By adjusting the dosage of triethylamine and 4-methoxysulfonamide, multifunctional ionic polymers PFMA-1, PFMA-2, PFMA-3 and PFMA-4 can be prepared respectively, wherein the dosage of the first organic medium, the second organic medium, triethylamine and 4-methoxysulfonamide is shown in Table 1:

[0148] Table 1

[0149]

[0150]

[0151] The structural formula, EW and grafting rate of PFMA-1, PFMA-2, PFMA-3 and PFMA-4 are shown in Table 2:

[0152] Table 2

[0153]

[0154] Example 2

[0155] (1) Weigh 1 g of sulfonyl fluoride resin 2 and dissolve it in 12 mL of a mixed solvent (acetonitrile: hexafluorobenzene, volume ratio 2:10);

[0156] (2) dispersing 0.25 g of 4-ethoxybenzenesulfonamide in 6 mL of DMAc to obtain a functionalization reagent solution;

[0157] (3) The swollen sulfonyl fluoride resin and the functionalizing agent solution were mixed in a flask, and then 4 g of triethylamine was added dropwise at 20°C. The reaction system was then heated to 80°C and stirred for 48 hours. After the reaction was completed, the reaction system was poured into acetone to separate the polymer solid and the small molecules, and acetone and cyclohexane were used to wash alternately. The multifunctional ionic polymer PFMA-5 was obtained by vacuum drying at 45°C for 48 hours.

[0158] Wherein, the structural formula of sulfonyl fluoride resin 2 is:

[0159]

[0160] The grafting rate of PFMA-5 is 46.5%, and the structural formula is:

[0161]

[0162] Example 3

[0163] (1) Weigh 1 g of sulfonyl fluoride resin 2 and dissolve it in 12 mL of a mixed solvent (acetonitrile: hexafluorobenzene, volume ratio 2:10);

[0164] (2) dispersing 1.42 g of 4-trifluoromethoxybenzenesulfonamide in 6 mL of DMAc to obtain a functionalization reagent solution;

[0165] (3) The swollen sulfonyl fluoride resin and the functionalizing agent solution were mixed in a flask, and then 4 g of triethylamine was added dropwise at 20°C. The reaction system was then heated to 80°C and stirred for 48 hours. After the reaction was completed, the reaction system was poured into ethanol to separate the polymer solid and small molecules, and then washed alternately with ethanol and butanone, and then placed in 8 mol / L potassium hydroxide solution at 80°C for potassiumization for 24 hours. The solid product was washed with water to a neutral washing solution, and vacuum dried at 45°C for 48 hours to obtain the multifunctional ionic polymer PFMA-6.

[0166] The EW of PFMA-6 is 1263 g / mol, the grafting rate is 95.0%, and the structural formula is:

[0167]

[0168] Example 4

[0169] (1) Weigh 1 g of sulfonamide resin 3 and dissolve it in 15 mL of anhydrous DMF to form a polymer solution, add 2 mL of xylene and 1 g of 3-methoxybenzenesulfonyl fluoride, stir to dissolve, and then drop 5 g of tripropylamine;

[0170] (2) The reaction system was then heated to 140°C and stirred for 24 hours. After the reaction was completed, the reaction system was poured into 100 mL of dichloromethane for precipitation, and was washed alternately with acetone and cyclohexane, and then dried under vacuum at 50°C for 24 hours to obtain a multifunctional polymer PFMA-7.

[0171] (3) 0.5 g of PFMA-7 was acidified in a 1 mol / L sulfuric acid solution at 60°C for 24 h. The acidified solid product was washed alternately with acetone and ethyl acetate until the pH value of the washing solution reached 6.5 to 7.5. The multifunctional polymer PFMA-8 was obtained by vacuum drying at 45°C for 48 h. The EW of PFMA-8 was 886 g / mol.

[0172] Sulfonamide resin 3 is obtained by reacting sulfonyl fluoride resin with ammonia, and its structural formula is:

[0173]

[0174] The grafting rates of PFMA-7 and PFMA-8 are both 90.3%, and the structural formulas are:

[0175]

[0176] Example 5

[0177] (1) Weigh 1 g of sulfonamide resin 2 and dissolve it in 10 mL of anhydrous NMP. Add 5 mL of anhydrous DMSO and 1.19 g of 4-butoxybenzenesulfonyl chloride, stir to dissolve, and then drop 5 g of tributylamine.

[0178] (2) The reaction system was then heated to 160°C and stirred for 10 hours, then heated to 180°C and stirred for 2 hours. After the reaction, the reaction system was poured into 100 mL of ethanol to wash the solid product, which was then washed alternately with ethanol and cyclohexane, then added to a 1 mol / L sulfuric acid solution and acidified at 60°C for 2 hours, washed with water until neutral, and then dried in a vacuum at 50°C for 24 hours to obtain a multifunctional polymer PFMA-9.

[0179] The structural formula of sulfonamide resin 2 is:

[0180]

[0181] The EW of PFMA-9 is 1257 g / mol, the grafting rate is 98.5%, and the structural formula is:

[0182]

[0183] Example 6

[0184] (1) Weigh 20 g of sulfonamide resin 1 and dissolve it in 300 mL of anhydrous DMAc to form a polymer emulsion. Add 24.4 g of 4-methoxybenzenesulfonyl chloride and 50 g of tripropylamine. Stir and mix in a flask under nitrogen atmosphere for 10 min.

[0185] (2) Raise the temperature to 145°C and stir the reaction for 36 hours. Add the reaction product to acetone to precipitate the solid product, wash it alternately with dichloromethane and acetone, and acidify it in 6 mol / L hydrochloric acid at 80°C for 24 hours. Wash the acidified solid product with butanone until the pH value of the washing solution reaches 6.5-7.5. Vacuum dry it at 45°C for 72 hours to obtain a clean multifunctional polymer PFMA-10. The grafting rate of PFMA-10 is 100%, and the EW is 1005 g / mol.

[0186] The structural formula of sulfonamide resin 1 is:

[0187]

[0188] Example 7

[0189] (1) Weigh 20 g of sulfonamide resin 4 and dissolve it in 250 mL of anhydrous DMSO to form a polymer solution, add 28.7 g of 3-methoxybenzenesulfonyl chloride, and then add 50 g of tributylamine. Stir and mix in a flask under nitrogen atmosphere for 10 min.

[0190] (2) Raise the temperature to 155°C and stir the reaction for 15 hours, then raise the temperature to 180°C and stir the reaction for 3 hours. Add the reaction product to dichloromethane to precipitate the solid product, wash it with acetone, and acidify it in 6 mol / L hydrochloric acid at 80°C for 24 hours. Wash the acidified solid product with butanone until the pH value of the washing solution reaches 6.5-7.5. Vacuum dry it at 45°C for 72 hours to obtain a clean multifunctional polymer PFMA-11. The grafting rate of PFMA-11 is 100%, and the EW is 876 g / mol.

[0191] The structural formula of sulfonamide resin 4 is:

[0192]

[0193] The structural formula of PFMA-11 is:

[0194]

[0195] Example 8

[0196] Weigh 0.5g of PFMA-2 in Example 1 and dissolve it in 10mL DMAc, add 1.5g urea, 1.5g dicyandiamide and 2g orthophosphoric acid, stir and react at 150°C for 12h, pour into 50mL acetone to precipitate the polymer, rinse with water to neutrality, and freeze-dry at -20 to 0°C for 48h to obtain the multifunctional ionic polymer PFMA-12. The hydroxyl groups on the benzene ring of the side chain of PFMA-2 are completely reacted into phosphonic acid groups, and the grafting rate of PFMA-12 is the same as that of PFMA-2.

[0197] Example 9

[0198] Weigh 0.5g of PFMA-3 in Example 1 and dissolve it in 10mL DMF, add 1g urea, 1g dicyandiamide and 1.5g orthophosphoric acid, stir and react at 135°C for 12h, pour into 50mL acetone to precipitate the polymer, rinse with water to neutrality, freeze-dry at -20 to 0°C for 48h to obtain the multifunctional ionic polymer PFMA-13. The hydroxyl groups on the benzene ring of the side chain of PFMA-3 are completely reacted into phosphonic acid groups, and the grafting rate of PFMA-13 ​​is the same as that of PFMA-3.

[0199] Example 10

[0200] Weigh 0.5 g of PFMA-4 in Example 1 and dissolve it in 10 mL of DMSO, add 0.5 g of urea, 0.5 g of dicyandiamide and 0.5 g of orthophosphoric acid, stir and react at 160° C. for 10 h, pour into 50 mL of acetone to precipitate the polymer, rinse with water to neutrality, and freeze-dry at -20 to 0° C. for 48 h to obtain the multifunctional ionic polymer PFMA-14. The hydroxyl groups on the benzene ring of the side chain of PFMA-4 are completely reacted into phosphonic acid groups, and the grafting rate of PFMA-14 is the same as that of PFMA-4.

[0201] The structural formulas of PFMA-12, PFMA-13 ​​and PFMA-14 are:

[0202]

[0203] Embodiment 11

[0204] Weigh 0.5 g of PFMA-11 in Example 7, dissolve it in 10 mL of DMAc, add 1.25 g of urea, 1.5 g of dicyandiamide and 1.8 g of orthophosphoric acid, stir and react at 150 ° C for 12 h, pour into 50 mL of acetone to precipitate the polymer, rinse with water to neutrality, and freeze-dry at -20 to 0 ° C for 48 h to obtain the multifunctional ionic polymer PFMA-15.

[0205] Example 12

[0206] Different from Example 11, the reaction time is 2 hours to obtain the multifunctional ionic polymer PFMA-16.

[0207] Example 13

[0208] Different from Example 11, the reaction time is 30 min, and the multifunctional ionic polymer PFMA-17 is obtained.

[0209] Embodiment 14

[0210] Different from Example 11, the reaction time is 3 minutes, and the multifunctional ionic polymer PFMA-18 is obtained.

[0211] Embodiment 15

[0212] Different from Example 11, the reaction temperature is 80° C., and a multifunctional ionic polymer PFMA-19 is obtained.

[0213] The structural formulas of PFMA-15, PFMA-16, PFMA-17, PFMA-18 and PFMA-19 are:

[0214]

[0215] Example 16

[0216] Weigh 15g of PFMA-10 in Example 6, dissolve in 200mL DMAc, add 25g urea, 30g dicyandiamide and 35g orthophosphoric acid, stir and react at 150°C for 12h, pour into 600mL dichloromethane to precipitate the polymer, rinse with acetone until neutral, and vacuum dry at 45°C for 48h to obtain the multifunctional ionic polymer PFMA-20. The hydroxyl groups on the side chain benzene ring of PFMA-10 are completely reacted to phosphonic acid groups, and the grafting rate of PFMA-20 is the same as that of PFMA-10. The structural formula of PFMA-20 is:

[0217]

[0218] Embodiment 17

[0219] Weigh 0.25 g of the multifunctional ionic polymer PFMA-2, PFMA-3 or PFMA-4 in Example 1, dissolve it in 4.75 g of DMAc, cast it in an ultra-flat culture dish, dry it at 80°C for 12 h, and heat treat it at 140°C for 5 min to obtain ion exchange membranes PEM-2, PEM-3 or PEM-4 with an average thickness of 50 μm, respectively.

[0220] Embodiment 18

[0221] 0.5 g of PFMA-15 in Example 11 was weighed and dissolved in 4.5 g of DMSO, cast in an ultra-flat culture dish and dried at 80° C. for 12 h, and vacuum heat treated at 160° C. for 5 min to obtain an ion exchange membrane PEM-15 with an average thickness of 100 μm.

[0222] Embodiment 19

[0223] 1 g of PFMA-1 in Example 1 was weighed and dissolved in 4 g of DMSO, cast in an ultra-flat petri dish, dried at 80° C. for 12 h, and vacuum heat treated at 160° C. for 5 min to obtain an ion exchange membrane PEM-1 with an average thickness of 200 μm. The IEC of PEM-1 was 1.00 mmol / g.

[0224] Embodiment 20

[0225] 15 g of PFMA-11 in Example 7 was weighed and dissolved in 85 g of a mixed solvent (water: ethanol: n-propanol: DMF = 2:2:4:1, mass ratio) to obtain resin slurry A. The resin slurry A was coated on both sides of the ePTFE-1, dried at 100° C. for 5 min, and heat treated at 140° C. for 3 min to obtain an ion exchange membrane PEM-11-5 with an average thickness of 5 μm. The IEC of PEM-11-5 was 0.97 mmol / g.

[0226] Embodiment 21

[0227] The resin slurry A in Example 20 was coated on both sides of the ePTFE-3, dried at 100° C. for 15 min, and heat treated at 140° C. for 3 min to obtain an ion exchange membrane PEM-11-25 with an average thickness of 25 μm. The IEC of PEM-11-25 was 1.20 mmol / g.

[0228] Embodiment 22

[0229] 5 g of PFMA-10 in Example 6 was weighed and dissolved in 20 g of a mixed solvent (water: ethanol: n-propanol = 2:5:1, mass ratio) to obtain resin slurry B. The resin slurry B was coated on both sides of the ePTFE-2, dried at 100° C. for 5 min, and heat treated at 140° C. for 3 min to obtain an ion exchange membrane PEM-10 with an average thickness of 12 μm.

[0230] Embodiment 23

[0231] 5 g of PFMA-20 in Example 16 was weighed and dissolved in 20 g of a mixed solvent (water: ethanol: isopropanol = 2:5:1, mass ratio) to obtain resin slurry C. The resin slurry C was coated on both sides of the ePTFE-2, dried at 100° C. for 5 min, and heat treated at 160° C. for 5 min to obtain an ion exchange membrane PEM-20 with an average thickness of 11.6 μm.

[0232] Embodiment 24

[0233] The PEM-20 in Example 23 was heat treated at 140° C. for 4 h, then immersed in 2 mol / L hydrochloric acid at 60° C. for 4 h, and then immersed in deionized water for 24 h to remove excess hydrochloric acid to obtain an ion exchange membrane PEM-20H.

[0234] Comparative Example 1

[0235] Weigh 0.25g of perfluorosulfonic acid resin 1 and dissolve it in 4.75g of DMAc, cast it in an ultra-flat petri dish, dry it at 80℃ for 12h, and heat treat it at 140℃ for 5min to obtain an ion exchange membrane D-PEM-2 with an average thickness of 50μm. The EW of perfluorosulfonic acid resin 1 is 850g / mol, and the structural formula is:

[0236]

[0237] Comparative Example 2

[0238] Different from Example 7, the functionalizing agent is 24.5 g of benzenesulfonyl chloride, and the ionic polymer D-PFMA-15 is obtained. The EW of D-PFMA-15 is 859 g / mol, and the structural formula is:

[0239]

[0240] Comparative Example 3

[0241] 0.5 g of D-PFMA-15 in Comparative Example 2 was weighed and dissolved in 4.5 g of DMSO, cast into an ultra-flat petri dish, dried at 80° C. for 12 h, and vacuum heat treated at 160° C. for 5 min to obtain an ion exchange membrane D-PEM-15 with an average thickness of 100 μm.

[0242] Comparative Example 4

[0243] 5 g of PFIA resin was weighed and dissolved in 20 g of a mixed solvent (water: ethanol: isopropanol = 2:5:1, mass ratio) to obtain resin slurry D. The resin slurry D was coated on both sides of the ePTFE-2, dried at 100° C. for 5 min, and heat treated at 160° C. for 5 min to obtain an ion exchange membrane D-PEM-20 with an average thickness of 11.3 μm.

[0244] The EW of PFIA is 625 g / mol, and the structural formula is:

[0245]

[0246] Comparative Example 5

[0247] The D-PEM-20 in Comparative Example 4 was heat treated at 140° C. for 4 h, then immersed in 2 mol / L hydrochloric acid at 60° C. for 4 h, and then immersed in deionized water for 24 h to remove excess hydrochloric acid to obtain an ion exchange membrane D-PEM-20H.

[0248] Performance Testing

[0249] The test methods for conductivity, EW, IEC, water absorption and mechanical properties refer to GB / T20042.3-2022 "Proton exchange membrane fuel cell part 3: proton exchange membrane test method".

[0250] Fuel cell polarization curve: The test method refers to GB / T20042.5-2022 "Proton exchange membrane fuel cell Part 5: Membrane electrode test method".

[0251] Free radical resistance of ion exchange membrane: The ion exchange membrane was immersed in Fenton's reagent at 80°C for 8 hours, and the mass loss and conductivity decay before and after immersion were compared. Preparation of Fenton's reagent: 50 mL of 3% H 2 O 2 0.1 mL of Fe with a molar concentration of 0.01 mol / L was added to the solution. 2+ The solution is the Fenton reagent, which is prepared and used immediately. The smaller the mass loss percentage, the better the durability.

[0252] Table 3 shows the IEC, water absorption, tensile strength, elastic modulus and free radical resistance of the ion exchange membranes in Example 17, Example 18, Comparative Example 1 and Comparative Example 3. Table 4 shows the conductivity at different relative humidities. The test temperatures of the conductivity are 80° C. and 90° C., respectively, and the relative humidities are 50% and 80%, respectively.

[0253] Table 3

[0254]

[0255] Table 4

[0256]

[0257] Compared with D-PEM-2, the IEC and water absorption of PEM-4, PEM-3 and PEM-2 gradually decrease with the increase of the grafting rate of multifunctional ionic polymer. The relative molecular mass of sulfonyl imide side chain is higher than that of sulfonic acid side chain, which will increase EW and reduce the IEC of the material. Lower IEC and longer sulfonyl imide side chain structure will reduce the water absorption of ion exchange membrane. The ion transport capacity of sulfonyl imide group is better than that of sulfonic acid group under high temperature and low humidity conditions. Under 50% RH conditions, the conductivity at different temperatures increases with the increase of multifunctional ionic polymer grafting rate. Sulfonic acid group and sulfonyl imide group have good ion transport capacity at 80℃ and 80% RH. PEM-3 and PEM-4 containing sulfonic acid group and sulfonyl imide group have high conductivity. The two ionic groups show good synergistic effect under appropriate conditions. Under the conditions of 90℃ and 80%RH, the sulfonic acid group is easy to lose water, resulting in a decrease in ion transmission capacity. Multifunctional ion exchange polymers with high grafting rates show better electrochemical properties. The higher tensile strength and tensile modulus of multifunctional ion polymers are mainly due to three factors. First, they have a longer side chain structure, which can promote the formation of hydrophilic and hydrophobic phase separation structure; second, the end group of the side chain is a rigid phenyl group, which is conducive to the improvement of modulus; third, the phenolic hydroxyl and acidic ion groups between different side chains form a long-range hydrogen bond network, which is conducive to the improvement of mechanical properties. The materials of PEM-2, PEM-3 and PEM-4 contain CH structures with poor free radical resistance, but because the phenyl group contains phenolic hydroxyl substituents, the phenolic hydroxyl group acts as a free radical quencher to improve the free radical resistance and antioxidant properties of the material. The free radical resistance of PEM-2, PEM-3 and PEM-4 is not significantly different from that of the perfluorinated structure D-PEM-2.

[0258] Compared with D-PEM-15, PEM-15 has two acidic groups on the side chain of PFMA-15, which has a higher IEC. The phosphonic acid group is amphoteric, and in PEM-15, it has both the characteristics of a proton acid, which can transfer protons and perform proton compensation, and the characteristics of a Lewis base, which can ionically cross-link with the strongly acidic sulfonimide group to improve the mechanical properties, dimensional stability and chemical stability of the material. Therefore, PEM-15 has a higher IEC, a water absorption rate similar to that of D-PEM-15, and better mechanical properties and chemical stability.

[0259] Table 5 shows the IEC, water absorption, and conductivity of the ion exchange membranes in Example 22, Example 23, Example 24, Comparative Example 4, and Comparative Example 5. The temperature for the conductivity test is 80° C. and the relative humidity is 80%.

[0260] Table 5

[0261] Ion exchange membrane IEC(mmol / g) Water absorption (%) Conductivity (mS / cm) Embodiment 23 PEM-10 0.87 25 69 Embodiment 23 PEM-20 1.37 27 145 Embodiment 23 PEM-20H 1.37 27 143 Comparative Example 4 D-PEM-20 1.39 28 168 Comparative Example 5 D-PEM-20H 1.11 22 92

[0262] Compared with D-PEM-20, PEM-20 has similar water absorption, and PEM-20 has lower IEC and conductivity. This is because the phosphonic acid group is amphoteric, which will crosslink with some sulfonyl imide groups to reduce the ion exchange capacity. At the same time, the phosphonic acid group has the characteristics of a monoacid and can only ionize one hydrogen ion, which has a limited increase in ion exchange capacity. The sulfonic acid group has better ion transmission capacity than the phosphonic acid group under 80°C and 80% RH conditions, and the IEC of D-PEM-20 is higher, so it has higher conductivity. In terms of water absorption, the molar ratio of tetrafluoroethylene repeating units in PFIA resin is higher, with better crystallinity, which can effectively control water absorption and swelling. The crystallinity of PFMA-20 is weaker than that of PFIA resin, but the hydrophilicity of the phosphonic acid group is lower than that of the sulfonic acid group, and the ionic crosslinking effect of the phosphonic acid group and the strong acid group can effectively reduce the water absorption. Both PEM-20 and D-PEM-20 have suitable water absorption.

[0263] The cross-sectional SEM images of PEM-20 and D-PEM-20 are shown in Figure 2. Figure 2 As shown, from Figure 2 It can be seen that both materials have good filling effects in the reinforcement layer.

[0264] The performance of PEM-20H and PEM-20 is basically the same. The IEC, water absorption and conductivity of D-PEM-20H are significantly lower than those of D-PEM-20. The side chain structure of PFIA is unstable at high temperature and will degrade into sulfonamide groups. After acidification, it will be converted into sulfonic acid groups. The sulfonimide groups on a single side chain will fall off, leaving only sulfonic acid groups. There is a large sterically hindered phenyl spacer between the sulfonimide group and the sulfonic acid group of PFMA-20, which cannot form an anhydride structure in the side chain and thus leads to the degradation of the side chain. It can also effectively reduce the probability of anhydride formation between side chains. PEM-20 has good thermal stability under high temperature conditions, and its performance remains basically unchanged, while PFIA undergoes obvious degradation reactions at high temperatures and has poor high temperature stability.

[0265] The polarization curves of PEM-20H and D-PEM-20H are shown in Figure 3 As shown, from Figure 3 It can be seen that under the conditions of 80℃ and 65%RH, the membrane electrode power density prepared by PEM-20H reaches 1444.8mW / cm2@0.6V, which is better than 937mW / cm2@0.6V of D-PEM-20H, and has lower internal resistance and better fuel cell single cell performance.

[0266] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0267] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A multifunctional ionic polymer, characterized in that: The multifunctional ionic polymer comprises at least one compound having a structural formula as shown in formula (1): Wherein, x is 3 to 14, y is 1 to 10000; z×100%≥1%; a=a positive integer of 0 to 6, b=a positive integer of 2 to 5; R0 is selected from any one of OM, F, Cl, Br, I or NH2; R1 is an alkylene group, a fluoroalkylene group or a direct bond; R2 is selected from any one of a C1-C6 alkyl group, a C1-C6 fluoroalkyl group, M or PO(OM)2; R5 and R6 are each independently selected from any one of H, F, Cl, Br, a C1-C6 alkyl group or a C1-C6 fluoroalkyl group; and M is selected from any one of hydrogen, lithium, sodium, potassium, rubidium, cesium, ammonium ion or tertiary ammonium cation.

2. The multifunctional ionic polymer according to claim 1, characterized in that The EW of the multifunctional ionic polymer is 400 to 2000 g / mol.

3. The multifunctional ionic polymer according to claim 1, characterized in that The multifunctional ionic polymer includes a first polymer and a second polymer; The structural formula of the first polymer is shown in formula (2): wherein a, b, x, y, z, M, R1, R5, and R6 are the same as those in formula (1); and R4 is selected from any one of M, a C1-C6 alkyl group, and a C1-C6 fluoroalkyl group; The structural formula of the second polymer is shown in formula (3): wherein a, b, x, y, z, M, R1, R5, and R6 are the same as those in formula (1), and R7 is selected from PO(OH)2.

4. The method for preparing a multifunctional ionic polymer according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) dispersing a resin raw material and a functionalizing agent in a first organic medium, and then adding an organic base to carry out a nucleophilic substitution reaction to obtain a crude product dispersion; (2) pouring the crude product dispersion obtained in step (1) into a poor solvent for separation to obtain a crude polymer product, and drying the crude polymer product to obtain an intermediate product; (3) The intermediate obtained in step (2) is transformed by an alkaline solution and / or an acid solution, washed with water and / or a poor solvent, and then dried to obtain a first polymer.

5. The method for preparing a multifunctional ionic polymer according to claim 4, characterized in that: In the step (1), the resin raw material is a sulfonyl halide resin, and the functionalizing agent is a sulfonamide compound; or, the resin raw material is a sulfonamide resin, and the functionalizing agent is a sulfonyl halide compound; And / or, in the step (1), the first organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetramethyl sulfoxide, hexamethylphosphoric triamide, N-methylpyrrolidone or tetrahydrofuran; And / or, in the step (1), the organic base comprises at least one of an organic amine or a nitrogen heterocyclic compound that does not contain a nitrogen heterocyclic ring, and the organic amine that does not contain a nitrogen heterocyclic ring comprises C1 to C 20 Alkyl and / or C6~C 20 At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group, wherein the nitrogen heterocyclic compound comprises C1 to C 20 Alkyl and / or C6~C 20 At least one of pyridine, imidazole, pyrrole, piperidine or piperazine substituted with an aromatic group; And / or, in the step (1), the mass ratio of the resin raw material, the functionalizing agent and the organic base is 100:1-400:1-800; And / or, in the step (1), the temperature of the nucleophilic substitution reaction is 50 to 180° C., the reaction pressure is 0.1 to 10 MPa, and the reaction time is 1 h to 120 h; and / or, in step (2) and / or step (3), the poor solvent comprises at least one of lipids, aromatic hydrocarbons, alkanes, ketones or halogenated hydrocarbons; And / or, in step (3), the alkaline solution includes at least one of lithium hydroxide solution, rubidium hydroxide solution, cesium hydroxide solution, ammonia solution, NaOH solution, and KOH solution, and the acid solution includes at least one of sulfuric acid solution, nitric acid solution, phosphoric acid solution, or hydrochloric acid solution; And / or, in the step (3), the temperature of the transformation treatment is 20 to 100° C., and the time of the transformation treatment is 1 to 48 hours.

6. The method for preparing a multifunctional ionic polymer according to claim 4, characterized in that: The step (1) comprises: dispersing the resin raw material in a first organic medium to obtain a resin raw material dispersion, dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution, mixing the resin raw material dispersion and the functionalizing agent solution, and then adding an organic base to perform a nucleophilic substitution reaction to obtain a crude product dispersion; Preferably, the second organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethyl sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone or tetrahydrofuran.

7. The method for preparing a multifunctional ionic polymer according to claim 4, characterized in that: The method further comprises the step (4): adding the first polymer and the phosphonating agent into a third medium for a phosphonating reaction to obtain a second polymer; Preferably, the third medium comprises at least one of water, polyols, fatty alcohols, DMF, DMAc, DMSO or tetrahydrofuran; And / or, the phosphonating agent includes at least one of orthophosphoric acid, oligophosphoric acid, alkali metal salt or ammonium salt of oligophosphoric acid, sodium hexametaphosphate, phosphorus trichloride, phosphorus pentachloride, phosphorus oxychloride, and triester phosphite compound; And / or, the phosphonation reaction is carried out under the action of a catalyst, the catalyst comprises at least one of urea, urea derivatives, guanidine, guanidine derivatives, trimethylamine or triethylamine, and the mass ratio of the first polymer, the phosphonation agent and the catalyst is 1:0.2-10:0-15; And / or, the temperature of the phosphonation reaction is 20 to 180° C., and the time of the phosphonation reaction is 1 min to 24 h.

8. The method for preparing a multifunctional ionic polymer according to claim 4, characterized in that: In the step (2), the structure of the intermediate is as shown in formula (1), wherein a, b, x, y, z, M, R1, R5, and R6 are the same as those in formula (1), R0 is selected from F, C1, Br, I or NH2, and R2 is selected from any one of M, C~C6 alkyl, and C~C6 fluoroalkyl.

9. The method for preparing a multifunctional ionic polymer according to claim 8, characterized in that: The preparation method further comprises: adding the intermediate and the phosphonating agent into a third medium for a phosphonating reaction to obtain a third polymer, wherein the structural formula of the third polymer is shown in formula (4): Among them, a, b, x, y, z, M, R0, R1, R5, and R6 are the same as those in the intermediate, R8 is PO(OM)2, and R2 in the intermediate is H.

10. Use of the multifunctional ionic polymer according to any one of claims 1 to 3 or the multifunctional ionic polymer prepared by the preparation method according to any one of claims 4 to 9 in ion exchange membranes.

11. An ion exchange membrane, characterized in that: The invention comprises the multifunctional ionic polymer described in any one of claims 1 to 3 or the multifunctional ionic polymer prepared by the preparation method described in any one of claims 4 to 9.

12. The method for preparing an ion exchange membrane according to claim 11, characterized in that: The following steps are involved: (a) dispersing the multifunctional ionic polymer according to any one of claims 1 to 3 or the multifunctional ionic polymer prepared by the preparation method according to any one of claims 4 to 9 in a solvent to obtain a resin slurry; (b) forming and drying the resin slurry obtained in step (a) to obtain an ion exchange membrane.

13. Application of the ion exchange membrane according to claim 11 or the ion exchange membrane prepared by the preparation method according to claim 12 in batteries, chlor-alkali industry, water electrolysis hydrogen production, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.

Citation Information

Cited By

  • Proton exchange resin with multi-element proton conduction center and preparation method thereof

    CN120040648A